1992
DOI: 10.3348/jkrs.1992.28.1.61
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the diffuse axonal injury

Abstract: CT has facilitated early recognition a nd treatment of focal brain injuries in patients with h ead trauma. However.CT shows relatively low sensitivity in identifying nonhemorrhagic contusion and injuries of white matte r MR is known to be supe rior to CT in detection of white matter injuries' s uch as diffuse axonal injury. MR imaging in 14 cases of diffuse a xonal injury on 2.0T was studied. The corpus callosum. especially the body portion. was the most commonly involved site. The lesions ranged from 5 to 20m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Metal nanoparticles are opening exciting perspectives in chemistry, physics and medicine, thanks to the possibility of incorporating new and relevant properties1–7 through their surface functionalization with molecules, surfactants and polymers. For this purpose, molecules can be anchored on the nanoparticles by using suitable groups to interact with the surface, promoting in some cases specific orientation of the adsorbate 8–11. In the particular case of gold, silver and copper nanoparticles, the adsorbates exposed to the surface plasmons can be probed by means of the surface‐enhanced Raman scattering (SERS) effect, through the strong enhancement of selected vibrational peaks of the molecules 12.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles are opening exciting perspectives in chemistry, physics and medicine, thanks to the possibility of incorporating new and relevant properties1–7 through their surface functionalization with molecules, surfactants and polymers. For this purpose, molecules can be anchored on the nanoparticles by using suitable groups to interact with the surface, promoting in some cases specific orientation of the adsorbate 8–11. In the particular case of gold, silver and copper nanoparticles, the adsorbates exposed to the surface plasmons can be probed by means of the surface‐enhanced Raman scattering (SERS) effect, through the strong enhancement of selected vibrational peaks of the molecules 12.…”
Section: Introductionmentioning
confidence: 99%
“…In the surface-enhanced Raman (SERS) spectra, it has been previously documented that the presence of the n(CH) band indicates a vertical orientation of the aromatic adsorbates. [28,29] This observation might indicate the perpendicular orientation of BA on TiO 2 surfaces. Because of the absence of many modes representing the molecular symmetry, we could not apply the surface selection rules [28] for the present work.…”
Section: Infrared Spectra Of Ba On Tio 2 Powder Surfacesmentioning
confidence: 97%
“…[28,29] This observation might indicate the perpendicular orientation of BA on TiO 2 surfaces. Because of the absence of many modes representing the molecular symmetry, we could not apply the surface selection rules [28] for the present work. From the selection rule, [29] it was reported that the out-of-plane modes should be weakened for the perpendicular orientation of adsobates on surfaces.…”
Section: Infrared Spectra Of Ba On Tio 2 Powder Surfacesmentioning
confidence: 97%